Pendampingan dan Pengembangan Usaha UMKM Anis Tempe melalui Branding Produk di Era Digital - Damayanti, Adelia Ika; Nurhidayati, Anik; Ihsan, Sirojul; Aminur Rohman, M Hisyam (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
The development of Micro, Small, and Medium Enterprises (MSMEs) in the current digital era requires product branding through social media. Strengthening MSMEs product branding by providing business assistance through the Business Work Lecture (KKU) program conducted by YPPI Rembang University. In this case, the MSMEs assisted is MSMEs Anis Tempe which is located in Meteseh Kaliori Village, Rembang Regency, Central Java. The problems experienced by MSMEs Anis Tempe are at the marketing (branding) stage, lack of ability in digitalization, not having a business license and not having a business logo. The solution to this problem is to carry out a community service program with development and assistance in strengthening product branding through social media as a marketing strategy and expansion, as well as creating attractive logos and product labels. The results of this service activity are creating attractive logos and product labels, having a social media account, including the location of MSMEs on Google Maps, and having a business license continue their business. Keywords: Mentoring, MSMEs, Product Branding